Joint family consultations for psychiatric inpatients with severe eating disorders transitioning to adulthood: psychoanalytic design of a therapeutic setting - Putois, Olivier; Riegert, Myriam; Bahi, Nadine; Pires, Joël; De Luca, Manuella (Frontiers in Psychiatry, 2023)
While family work is acknowledged as relevant in the care of eating disorders (EDs), not much literature has explored it in the period of transition from adolescence to young adulthood (16-18 to 30 y.o.). Yet this period is of significant importance in the prognosis and evolution of EDs; but its particular stakes require specific therapeutic settings - especially for inpatient EDs. In this paper, we start from the paradoxical observation that some families refuse this type of work in its usual form, with a family-dedicated therapist, and require to only exchange with the psychiatrist in charge of the treatment plan. We use a psychosomatic-informed psychoanalytic approach to shed light on this refusal as a latent denial of the contribution of family dynamics to the current symptom, and an unconscious tendency to stick to a dependency-laden family scheme. We then explain the conception of a specifically dedicated therapeutic setting, designed to address this specific type of resistance, offered families as a therapeutic compromise designed to give them a specific position in the care of their child. In our Joint Therapeutic Consultations, family dynamics are addressed on the basis of exchanges regarding treatment and in particular feeding. While such exchanges are made possible by the latter’s presence, the therapeutic couple (psychiatrist-psychologist) uses them to address the parent and patient expectations underlying the symptom. We propose to call this “inscription”; it enables a separation from the underlying dependency-oriented family scheme, while stressing the importance to care for parental anxieties.